Digital Storytelling Through #Endsars.Com as A Form of Narative Memorial - Jayne I. Owan; Onyekachi Peter Onuoha (Pascasarjana Universitas Negeri Makassar, 2022)
Communal digital (auto) biographical is a memorial of trauma that exists in a synthetic frame referential to the memories of abuse. #Endsars.com highlights the collective narratives of netizens who are abused and subjugated by the Nigeria Police Force. Through the application of the concept of remembering, this study examines #Endsars.com as a digital memorial erected in the digital space by netizens through an autobiographical narrative method. This study employs a mixed-methods approach based on well-established social media research techniques and is founded on social media analytics and latent semantic analysis. This study observes that the Endsars.com narrative is a form of digital activism and resistance to police brutality in Nigeria. This paper submits that the (auto) biographical narrative style in Endsars.com is an expression of traumatic memories. This paper concludes that #Endsars.com amplifies the voices of those protesting against police brutality in the organic space. The study concludes that #Endsars.com is a digital Nigerian netizen memorial for victims of police brutality.